Was Ḥunayn ibn Isḥāq the Author of the Arabic Translation of Paul of Aegina's Pragmateia? Evidence from the Arabic Translations of the Hippocratic Aphorisms and the Syriac Lexicons of Bar Bahlul and Bar 'Ali. (18th August 2018) - Barry, Samuel G
Abstract: Study of the process of translation into Arabic of the Pragmateia of Paul of Aegina, an important work of late‐Hellenic medicine, has the potential to shed light upon the early development of Arabic medicine. Traditionally, the authorship of this translation has been ascribed to the famous translator Ḥunayn ibn Isḥāq. In this paper, however, I provide evidence drawn from several primary sources, including prominently the Arabic translations of the Hippocratic Aphorisms and the Syriac lexicons of Ḥasan bar Bahlul and Isho 'bar 'Ali, demonstrating that Ḥunayn was not the author of the Arabic translation of the Pragmateia, and that the translation was composed well before Ḥunayn's career. The addition of the Arabic version of the Pragmateia to the list of Arabic medical works produced prior to Ḥunayn should enrich significantly scholarly understanding of the early development of the discipline.